The effect of job insecurity on employees' job outcomes: the mediating role of job embeddedness - Safavi, Homayoun Pasha; Karatepe, Osman M. (Emerald Group Publishing Ltd, 2019)
Purpose Drawing on job embeddedness (JE) and reformulation of attitude theories, the purpose of this paper is to propose a conceptual model in which JE mediates the influence of job insecurity (JIS) on quitting intentions and service recovery performance (SRP). Design/methodology/approach Data came from 313 hotel service workers based on three waves through a two-week period in Iran. Service workers' SRP was rated by their direct supervisors. The abovementioned linkages were gauged using structural equation modeling. Findings All hypotheses are supported. Specifically, JIS diminishes JE. Consistent with the study's hypotheses, JE fosters SRP, while it reduces quitting intentions. As predicted, JE completely mediates the influence of JIS on propensity to quit and SRP. Originality/value What is known about how JIS can be mitigated is still scarce in the current literature. There is a paucity of evidence regarding the mechanism that links JIS to employee's outcomes.
Keywords: Quitting intentions; Job embeddedness; Job insecurity; Hotel employees; Service recovery performance